Routledge handbook on Arab media - Mīlādī, Nūr al-Dīn; Mellor, Noha, 1969- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This Handbook provides the first comprehensive reference book in English about the development of mass and social media in all Arab countries. Capturing the historical as well as current developments in the media scene, this collection maps the role of media in social and political movements. Contributors include specialists in the field from North America, Europe, and the Middle East. Each chapter provides an overview of the history, regulatory frameworks and laws governing the press, and socio-political functions of the media. While the geopolitical complexities of the region have been reflected in the expert analyses collectively, the focus is always the local context of each member state. All 37 chapters consider the specific historical, political and media trajectories in each country, to provide a contextual background and foundation for further study about single states or comparative analysis in two or more Arab states. Capturing significant technological developments and the widespread use of social media, this all-inclusive volume on Arab media is a key resource for students and scholars interested in journalism, media and Middle East studies"--
Algeria. Mass media in Algeria -- New and social media in Algeria -- Bahrain. Media in Bahrain - a contested sphere -- Egypt. Press in Egypt : impact on social and political transformations -- The Egyptian broadcasting sector between 1920 and 2020 -- Social media in Egypt : the debate continues -- Iraq. Iraqi press - between propaganda and sectarianism -- Broadcasting in Iraq - from pluralism to ethno-sectarianism -- Social media and social change in Iraq -- Jordan. The print and online media in Jordan - between liberalization and control -- Broadcast media in Jordan and the (rentier) state -- Kuwait. Chronicling Kuwait's media evolution : the politics of technology and regulation -- Lebanon. Whither the Lebanese press? The trials and tribulations facing the Lebanese print media -- Lebanese broadcasting : small country, influential media -- Libya. Media and social change in Libya -- Mauritania. Media in Mauritania : challenges and development -- Morocco. The Moroccan press : challenges and development -- Media configuration in Morocco -- The new and social media in Morocco -- Oman. Mass media for development - the media in the Sultanate of Oman -- Palestine. Palestinian media between partisanship and propaganda -- Palestinian new media -- Qatar. Media developments in Qatar -- Al Jazeera network and the transformations in the global communication flow -- Saudi Arabia. The Saudi press - the combined power of wealth and religion -- Saudi broadcasting media - a tool for regional influence -- The Janus-faced new media in Saudi Arabia -- Somalia. Mass media development in Somalia -- Internet and social media development in Somalia -- Sudan. Press in Sudan : models, regulatory frameworks, and development -- Radio and television broadcasting in Sudan -- Syria. The Syrian press and online media : a driver of Arabism -- The "soft" power of Syrian broadcasting -- Tunisia. Press in Tunisia : from French colonization to post-revolution era -- Broadcasting in Tunisia from independence to post-2011 revolution era -- Social media networks and the democratic transition in Tunisia : from censorship to freedom -- United Arab Emirates. Media in the UAE - creating a national voice -- Yemen. Media in Yemen - narratives of polarization and fragmentation.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 11, 2020).
Noureddine Miladi is Professor of Media and Communication at Qatar University, Qatar. He is former head of department of mass communication and president of the Arab Media & Communication Network (AMCN). He is editor of JAMMR, the first Arab refereed journal in Arab media and society. Noha Mellor is Professor of Media at the University of Bedfordshire, UK, and Adjunct Professor of Middle Eastern Studies at Stockholm University, Sweden. She is the author of several books about Arab media and journalism.
eBooks on EBSCOhost
Keywords: Mass media -- Arab countries; Social media -- Arab countries; Médias -- États arabes; Médias sociaux -- États arabes; SOCIAL SCIENCE / Media Studies; Mass media; Social media; Arab countries; handbooks; Handbooks and manuals; Guides et manuels